Sosialisasi Mitigasi Kebencanaan Berbasis Masyarakat Di Desa Peunayong - Anita rauzana Ruzana; Wira Dharma; M. Zardan (Asosiasi Dosen Akuntansi Indonesia, 2022)
In an effort to reduce disaster risk, disaster management activities need to be implemented as part of people's daily lives. The disaster management paradigm that has developed is more focused on preventing risk from arising, namely at the pre-disaster stage or known as risk management. At this stage strengthening community capacity in dealing with disasters is a very important part. Strengthening community capacity can be established by increasing the active participation of the community in various disaster management activities in Peunayong village in Banda Aceh. Indonesia is an area with a fairly high level of disaster risk, especially on the island of Sumatra including Banda Aceh, because on the island of Sumatra, especially Banda Aceh is an area that often occurs earthquakes, this is because the territory of Indonesia is located between the four Eurasian plates, the Indo-Australian plate, the Philippine plate and the Pacific plate, earthquakes with a magnitude of 7 on the Richter Scale or more often occur in areas around the meeting between these plates, for example the earthquake accompanied by the tsunami in 2004 that hit Aceh, which resulted in many casualties, considering Indonesia's special territory Banda Aceh often experiences earthquakes, so training and counseling on disaster management (disaster mitigation) are needed for the people in Banda Aceh. This community service program is carried out so that the community can prepare themselves and add insight in dealing with disasters, namely by counseling and training the community on disaster management/disaster mitigation.